Towards Theology of Parenthood: Mother Mary as the Role Model for Sensitive and Secure Christian Parenting - Ganc, Damijan (Verbum Vitae, 2024)
Mother Mary’s intimate and confidential relationship with God has inspired Christians around the world for the last two millennia. Her role in salvation history has already been discussed in detail in various church documents and scholarly literature. However, from an interdisciplinary point of view, her maternal role has not yet been fully evaluated from a psychological and child-rearing perspective. Therefore, in this article, we conduct a psychological analysis of the Gospel passages that talk about her maternal role and we evaluate these passages through the prism of the well-established attachment theory. Despite temporal and cultural differences, Mary’s maternal attitude is found to be highly consistent with the key findings in research on quality parenting and interpersonal relationships. As we show, her “maternal genius” is revealed through the following fundamental characteristics of attachment-focused parenting: unconditional acceptance, sensitive guidance, compassionate accompaniment and continuous emotional regulation. These characteristics of Mary’s motherhood come to the fore especially in the key moments of salvation history. The psychological analysis of Mary’s motherhood brings an important contribution to the “aggiornamento” of Mariology and enables some new opportunities for pastoral theology. With new scientifically supported insights, the Church will be better equipped to help parents to discover the beauty and depth of the mission of parenthood, following Mary’s example. The findings of our research therefore also represent an important foundation for the emerging theology of parenthood.